Tantangan Technopreneur Bagi Umkm Di Kota Bogor Sebagai Strategi Bertahan Di Era Pandemi Covid-19 - Mekaniwati, Ani; Nurendah, Yulia; Maulina, Dwi; Hanifah, Nadia Sabila (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The creation of entrepreneurs (entrepreneurs) is an alternative solution to various problems in society such as poverty and social inequality, increasing unemployment of productive age and depletion of energy supply reserves, all of which require creative and innovative actions. Technopreneur, one part of the development of entrepreneurship (entrepreneur) provides an overview of entrepreneurship by using technology-based innovation. With the technopreneurship development model, it can provide benefits or impacts, both economically, socially and environmentally. Technopreneurs can be interpreted as job creators who will actively encourage Indonesia to have a strong and competitive economic foundation. Inclusive economic growth and sustainable development need to continue to receive attention and support from various groups, namely the support of the government, the private sector, the community and of course support from academics in achieving the Sustainable Development Goals (SDGs). The economic impact is increasing efficiency and productivity, increasing income, creating new jobs and moving other economic sectors. Keywords: Entrepreneur, Technopreneur, MSME